An alternative wastewater treatment system for existing temporary UNIMAS campus - Jungan, F. (University Malaysia Sarawak, UNIMAS., 2000)
This dissertation describes the design of an alternative wastewater treatment system by Activated Sludge Process and subsequently recommends the suitable treatment schemes, which will minimize the overall impact on the environment and by the same token minimize the cost of the selected solution.